2022
DOI: 10.1007/s43039-022-00054-z
|View full text |Cite
|
Sign up to set email alerts
|

Issues in defining and placing consumer brand engagement

Abstract: The paper aims to identify the current positioning of consumer brand engagement (CBE) in marketing literature, thus filling a gap and contributing to a richer overview of the concept. Numerous research topics currently overlap in the marketing literature as brand theory has not been systemised precisely, especially with regard to consumer feeling towards brands and consumers’ active role in creating brand equity. The methodology adopted for this empirical research is qualitative, and the research question is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…While past research commonly regarded engagement as a multidimensional construct (Cantone et al , 2022), the discussions were predominantly consumer-based and ignored the firm-initiated perspective (Alvarez-Milán et al , 2018). Alvarez-Milán et al (2018) argued that customer engagement can be a firm-initiated resource and organizations normally take an active role to initiate engagement with customers.…”
Section: Engagement: An Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…While past research commonly regarded engagement as a multidimensional construct (Cantone et al , 2022), the discussions were predominantly consumer-based and ignored the firm-initiated perspective (Alvarez-Milán et al , 2018). Alvarez-Milán et al (2018) argued that customer engagement can be a firm-initiated resource and organizations normally take an active role to initiate engagement with customers.…”
Section: Engagement: An Overviewmentioning
confidence: 99%
“…Apart from the three-dimensional nature of engagement, prior research has identified the interactive nature of engagement (Cantone et al , 2022). In marketing, consumer–brand engagement focuses on “consumer/brand interactions” (Hollebeek et al 2014, p. 154), and customer engagement is an interaction between customers and brands through psychological processes (Vander Shee et al , 2020).…”
Section: Engagement: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations